Evolution of pollination by frugivorous birds in Neotropical Myrtaceae - María Gabriela Nadra; Norberto Pedro Giannini; Juan Manuel Acosta; Lone Aagesen (PeerJ, 2018)
Bird pollination is relatively common in the tropics, and especially in the Americas. In the predominantly Neotropical tribe Myrteae (Myrtaceae), species of two genera, Acca and Myrrhinium, offer fleshy, sugary petals to the consumption of birds that otherwise eat fruits, thus pollinating the plants in an unusual plant-animal interaction. The phylogenetic position of these genera has been problematic, and therefore, so was the understanding of the evolution of this interaction. Here we include new sequences of Myrrhinium atropurpureum in a comprehensive molecular phylogeny based on a balanced sample of two plastid and two nuclear markers, with the aim of providing the historical framework of pollination by frugivorous birds in Myrteae. We developed 13 flower and inflorescence characters that comprehensively depict the macroscopic morphological components of this interaction. Bayesian and parsimony phylogenies concur in placing both Acca and Myrrhinium in a clade with Psidium species; with Myrrhinium sister to Psidium. Mapping of morphological characters indicated some degree of convergence (e.g., fleshy petals, purplish display) but also considerable divergence in key characters that point to rather opposing pollination strategies and also different degrees of specialization in Acca versus Myrrhinium. Pollination by frugivorous birds represents a special case of mutualism that highlights the evolutionary complexities of plant-animal interactions.